2016
DOI: 10.1111/ijac.12582
|View full text |Cite
|
Sign up to set email alerts
|

Phase Evolution, Microstructure, and Mechanical Properties of Alumina–Mullite–Zirconia Composites Prepared by Iranian Andalusite

Abstract: This paper investigates the effects of Iranian andalusite and short milling times on alumina–mullite–zirconia composites. Andalusite powder was added at 0, 2.5, 5, and 10 wt% to an alumina–zircon mixture and the raw materials were milled for 1 or 3 h. The sintering of samples was carried out at the temperatures of 1550°C, 1600°C, and 1650°C for 3 h. Microstructural changes, phase composition, physical properties, and mechanical strength of the sintered composites were characterized by scanning electron microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Majidian et al [10] had studied the phase evolution and the microstructures of aluminamullite-zirconia composites mixed using Iranian andalusite and have shown similar results.…”
Section: Effect Of the Addition Of Andalusite On The Temperature And The Kinetics Of Zircon Decompositionmentioning
confidence: 83%
See 2 more Smart Citations
“…Majidian et al [10] had studied the phase evolution and the microstructures of aluminamullite-zirconia composites mixed using Iranian andalusite and have shown similar results.…”
Section: Effect Of the Addition Of Andalusite On The Temperature And The Kinetics Of Zircon Decompositionmentioning
confidence: 83%
“…It has been found that andalusite powder can reduce the decomposition temperature of zircon to 1600 °C [10,28] and accelerate the sintering of alumina-zircon, which leads to an increase of the mullite amount and improves the thermal shock resistance of the alumina-mullitezirconia composite.…”
Section: Effect Of the Addition Of Andalusite On The Temperature And The Kinetics Of Zircon Decompositionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, mullite formation and complication of reaction sintering demand high temperatures and longer times. To achieve this, some approaches such as incorporation of additives, 6,8,10,11 use of mineral industrial raw materials, 12 mechanical milling, 1,5,13 and microwave sintering 5,14 have been studied to promote the reaction sintering process and reduce the sintering temperature as well as energy consumption.…”
Section: Introductionmentioning
confidence: 99%